The efficacy of ginseng-containing traditional Chinese medicine in patients with acute decompensated heart failure: A systematic review and meta-analysis - Chen, Xiaozhe; Ma, Yulong; Li, Jianhua; Yao, Lei; Gui, Mingtai; Lu, Bo; Zhou, Xunjie; Wang, Mingzhu; Fu, Deyu (Frontiers in Pharmacology, 2023)
Objective: To evaluate the efficacy of ginseng-containing traditional Chinese medicine (TCM) for acute decompensated heart failure (ADHF). Methods: Seven databases were included from establishment until July 10, 2022. Pooled data were analyzed with random-effects model. The risk of bias was measured by the risk of bias tool for randomized trials (RoB 2). Modified Jadad scale score was used to assess the quality of including studies. The meta-analysis was performed with RevMan 5.3. Trial sequential analysis was assessed to avoid type I errors. Results: Twenty-eight articles were included. The results demonstrated that compared with conventional western therapy (WT), ginseng-containing TCM combined with WT further improved clinical efficacy (RR: 1.25, 95% CI: 1.20–1.29, P<0.00001, I2=8%), left ventricular ejection fraction (LVEF) (MD: 5.80, 95% CI: 4.86–6.74, P < 0.00001, I2=89%), stroke volume (MD: 13.80, 95% CI: 12.66 – 14.95, P < 0.00001, I2 = 93%), six-minute walk test (MD: 53.03, 95% CI: 20.76 – 85.29, P = 0.001, I2 = 97%), decreased 6-month rehospitalization (RR: 0.44, 95% CI: 0.18 – 1.11, P = 0.08, I2 = 0%), brain natriuretic peptide (MD: -188.12, 95% CI: -248.13 to -128.11, P<0.00001, I2 = 94%) , N-terminal pro-B-type natriuretic peptide (MD = -503.29; 95% CI: -753.18 to -253.40, P<0.0001, I2 = 89%) and Minnesota living heart failure questionnaire scores(MD: -9.68, 95% CI: -13.67 to -5.70, P<0.00001, I2=83%). The ROB2 assessment and modified Jaded scores showed most studies included were with some concerns. Conclusion: Compared with WT alone, ginseng-containing TCM is a possible way to benefit ADHF patients. However, limited by the quality of including trials, more high-quality studies are needed to provide reliable evidence.